Superexponentially convergent algorithm for an abstract eigenvalue problem with applications to ODEs - Gavrilyuk, I.P.; Makarov, V.L.; Romanyuk, N.M. (Нелінійні коливання, 2015)
A new algorithm for eigenvalue problems for the linear operators of the type A = A + B with a special application to high order ordinary differential equations is proposed and justified. The algorithm is based on the approximation of A by an operator A¯ = A + B¯ where the eigenvalue problem for A¯ is supposed to be simpler then that for A. The algorithm for this eigenvalue problem is based on the homotopy idea and for a given eigenpair number computes recursively a sequence of the approximate eigenpairs which converges to the exact eigenpair with an superexponential convergence rate. The eigenpairs can be computed in parallel for all prescribed indexes. The case of multiple eigenvalues of the operator A¯ is emphasized. Examples of the eigenvalue problems for the high order ordinary differential operators are presented to support the theory. Запропоновано та обґрунтовано новий алгоритм для задач на власнi значення для лiнiйних операторiв типу A = A + B iз спецiальним застосуванням до звичайних диференцiальних рiвнянь високого порядку. Алгоритм полягає в апроксимацiї оператора A таким оператором A¯ = = A + B, ¯ що задача на власнi значення для A¯ стає простiшою, нiж для A. Особливу увагу придiлено випадку, коли оператор A¯ має кратнi власнi значення. Запропонований пiдхiд базується на iдеї гомотопiї. Послiдовнiсть наближень до власних пар обчислюється в ходi рекурентного процесу та збiгається до точного розв’язку iз суперекспоненцiальною швидкiстю. Власнi пари можна обчислювати паралельно для всiх заданих iндексiв. Наведенi числовi приклади задач на власнi значення для звичайних диференцiальних операторiв високого порядку пiдтверджують одержанi теоретичнi результати.